2011
DOI: 10.1158/1078-0432.ccr-11-1762
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Antitumor Efficacy of Low-Dose Etoposide with Oncolytic Herpes Simplex Virus in Human Glioblastoma Stem Cell Xenografts

Abstract: Purpose Glioblastoma (GBM) inevitably recurs despite surgery, radiation and chemotherapy. A subpopulation of tumor cells, GBM stem cells (GSCs), has been implicated in this recurrence. The chemotherapeutic agent, etoposide is generally reserved for treating recurrent tumors, however its effectiveness is limited due to acute and cumulative toxicities to normal tissues. We investigate a novel combinatorial approach of low dose etoposide with an oncolytic HSV to enhance anti-tumor activity and limit drug toxicity… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 41 publications
2
64
0
1
Order By: Relevance
“…In addition, even those that were capable of primary sphere formation such as BT74, self-renewal was greatly impaired when BI2536 treatment was continued. Recently, BT74 cells have been shown to be resistant to chemotherapy and molecular-targeting agents [86,87]. Thus, our results are particularly exciting as it suggests that PLK1 inhibitor may potentially eliminate the cells that make up the bulk of the tumors as well as deplete the notoriously chemotherapy and radiation-resistant BTICs.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, even those that were capable of primary sphere formation such as BT74, self-renewal was greatly impaired when BI2536 treatment was continued. Recently, BT74 cells have been shown to be resistant to chemotherapy and molecular-targeting agents [86,87]. Thus, our results are particularly exciting as it suggests that PLK1 inhibitor may potentially eliminate the cells that make up the bulk of the tumors as well as deplete the notoriously chemotherapy and radiation-resistant BTICs.…”
Section: Discussionmentioning
confidence: 82%
“…To summarize, the tumor microenvironment, particularly as it relates to the potential contribution of immune suppression, heterogeneity of cells, and, potentially, GSCs, underscores the nature of the problem. Previous studies have suggested that GSCs are susceptible to treatment with oncolytic HSV (12,13). Until this study, syngeneic models of GSCs were sparse, and none that were suitable for examination of oHSV existed.…”
Section: Approaches To Treatmentmentioning
confidence: 97%
“…For Chou-Talalay analysis, fixed ratios of drug and/or virus were added to cells and the relative changes in cellular metabolism were used to calculate the combination index (CI) using the CompuSyn software (Version 1; Cambridge, MA, USA). 38,39 Virus burst size HS578T cells were infected with a specific MOI of KM100. Samples were harvested and tittered as described previously.…”
Section: Chou-talalay Analysismentioning
confidence: 99%